A review of family carers' experiences of hospital discharge for people with dementia, and the rationale for involving service users in health research - Mockford C (Dove Medical Press, 2015)
Carole Mockford Division of Health Sciences, Royal College of Nursing Research Institute, University of Warwick, Coventry, UK Abstract: In the UK, service user involvement is an important factor in health policy, and obtaining research funding. It may be helpful in expanding our knowledge in areas where research evidence is poor such as experiences of hospital discharge planning for the family carers of people with dementia. Methods: A rapid review. All study designs published in the English language were eligible for inclusion. Databases included: Medline, Embase, CINAHL, PsycInfo, Cochrane library and Web of Knowledge. A qualitative analysis was undertaken. Results: Four themes were identified: preparation for hospital discharge – dissatisfaction with being kept informed, discharge arrangements and management of conditions; little time to prepare. Communication between staff and families at discharge – insufficient communication regarding services, not being listened to and being undervalued as a resource could compromise post-discharge care. Support services post discharge – carers need help negotiating, and working with, services with regard to timing, and meeting requirements. Coping post hospital discharge – inadequate understanding about ability to cope, and patient's impairment, and family conflict over care may lead to unnecessary re-admission to hospital, or long term care. Evidence of specialist dementia models at discharge is described. Discussion: Carers are not always involved in hospital discharge planning as well as they might be. Issues are complex and depend on a number of factors. Poor communication can be overcome and carers can be better supported to cope post discharge as illustrated in the dementia models. The evidence base is weak but the absence of evidence does not indicate an absence of good practice. Conclusion: Carers who may feel their world is far removed from the academic world may not ordinarily participate in research studies. Service users, as co-researchers, may be able to improve trust and rapport between research and communities, collect fresh insights and gain deeper and more insightful data from participants. Keyword: hospital discharge, carers, dementia, user involvement